Ambidextrous workforces for managing market turbulence. Issue 5 (30th July 2019) - Caputo, Francesco; Giacosa, Elisa; Mazzoleni, Alberto; Ossorio, Mario
Abstract : Purpose: The purpose of this paper is to provide evidence regarding the contributions of ambidextrous workforces as a source of value for dynamic companies and organizations facing emerging market turbulence. Design/methodology/approach: Using structural equation modeling, the paper analyses the data collected via a semi-structured questionnaire administered to a sample of 1, 227 employees from 37 Italian small- to medium-sized enterprises to investigate the effect on companies' economic performance of ambidextrous workforce-related elements such as study background, previous work experience, work flexibility and soft capabilities. Findings: The research shows that multidisciplinary human resources' study background, previous human resources' work experience and human resources' soft capabilities are positively linked to companies' return on sales, providing indirect evidence about the role of ambidextrous workforces in supporting companies facing emerging market turbulence. Originality/value: The research demonstrates the relevant role of human resources in supporting companies to better align themselves to the emerging social and economic variety.